Quand les franges urbaines se mettent au vert : la nature aux marges de la métropole lyonnaise - Inès Méliani (Projets de Paysage)
The physiognomy of the Lyon metropolis is characterised by intense urban sprawl which has led to the disappearance of thousands of hectares of natural land. The city centre has gradually absorbed the outlying municipalities leaving behind islands of natural and agricultural lands. For a long time, these remaining spaces were seen as potential building land but today they are considered as spaces providing added value to public development projects. Taken into account upstream in the urban planning process these changing spaces, which have given rise to a variety of different landscapes, modes of use and methods of governance, have contributed to defining the urban fringes of Lyons. Urban planning documents of the Lyons agglomeration are evidence of the institutionalisation of a form of recreational nature through many examples which shed light on the problems relating to urban fringes : the redevelopment of the network of green spaces on the banks of the River Rhone, the deployment of “Nature Projects”, and the two major projects of the Miribel-Jonage Park to the north and the Gerland Park in a former brownfield to the south of the city. This study shows how the transitional spaces between Lyons and the countryside, long considered as complex areas to manage, are now perceived as assets in an urban planning policy aimed at improving quality of life and addressing new environmental issues.